(3UahI GdGNJjGQ aj CUhd Gdabgs - (3CHh eMeO YHO Gddg Hf MeRI Hf SdjeGf Hf MeRI GdMSfj Gdjefj,J (B614 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdMeO PQjYI ddQGZHjf ajg Edi CYdi GdeQGJH hHYO aEf GdYde (B_ (3hEf cKQJ afhfg aEf CLdg bOQkG HYO eYQaI Gddg hgPG gh GdeQGO HCUhd Gdabg s
(3BNQgG (B:s
(3hGYde Cf GdJaQbI Hjf GdYdI hGdSHH EfeG jUM Ydi QCi ef jefY ef JNUU GdYdI hHgPg GdeSCdI Je GdcJGH hGYde CfG bO JhNjfG ai gPG GdcJGH eWGHbI TjNfG hGLJgOfG ai eG ENJda ajg GdfXQ hGdMeO ddg s
(3HgG fXGe GdJYbjHIs
(3fSNI ebGHdIs
(3YdjgG Jedc HGSe Ydi Hf EHQGgje Hf YHO Gddg Hf EHQGgje Hf UdGM Hf GdgGOi GdbGSeis
(3Ydi WQJgG JedcGJ s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3CUhd Gdabgs